PTPσ Knockdown in Lampreys Impairs Reticulospinal Axon Regeneration and Neuronal Survival After Spinal Cord Injury - Rodemer, William; Zhang, Guixin; Sinitsa, Isabelle; Hu, Jianli; Jin, Li-qing; Li, Shuxin; Selzer, Michael E. (Frontiers in Cellular Neuroscience, 2020)
Traumatic spinal cord injury (SCI) results in persistent functional deficits due to the lack of axon regeneration within the mammalian CNS. After SCI, chondroitin sulfate proteoglycans (CSPGs) inhibit axon regrowth via putative interactions with the LAR-family protein tyrosine phosphatases, PTPσ and LAR, localized on the injured axon tips. Unlike mammals, the sea lamprey, Petromyzon marinus, robustly recovers locomotion after complete spinal cord transection (TX). Behavioral recovery is accompanied by heterogeneous yet predicable anatomical regeneration of the lamprey’s reticulospinal (RS) system. The identifiable RS neurons can be categorized as “good” or “bad” regenerators based on the likelihood that their axons will regenerate. Those neurons that fail to regenerate their axons undergo a delayed form of caspase-mediated cell death. Previously, this lab reported that lamprey PTPσ mRNA is selectively expressed in “bad regenerator” RS neurons, preceding SCI-induced caspase activation. Consequently, we hypothesized that PTPσ deletion would reduce retrograde cell death and promote axon regeneration. Using antisense morpholino oligomers, we knocked down PTPσ expression after TX and assessed the effects on axon regeneration, caspase activation, intracellular signaling, and behavioral recovery. Unexpectedly, PTPσ knockdown significantly impaired RS axon regeneration at 10 weeks post-TX, primarily due to reduced long-term neuron survival. Interestingly, cell loss was not preceded by an increase in caspase or p53 activation. Behavioral recovery was largely unaffected, although PTPσ knockdowns showed mild deficits in recovery of swimming distance and latency to immobility during open field swim assays. Although the mechanism underlying the cell death following TX and PTPσ knockdown remains unknown, this study suggests that PTPσ is not a net negative regulator of long tract axon regeneration in lampreys.